Product Islamization as a Marketing Strategy in the Resik V “Sekarang Berhijab” Advertisement in 2012 - Kolik Koirudin; Sri Kusuma Habsari; Deny Tri Ardianto (Lingua Cultura, 2020)
The research aimed to know why did Resik V transform its product advertisement by Islamization? How did the advertisement put and negotiate the Islamic symbols and codes on women’s feminine area cleansing products? The research would carry out textual data analysis for the 2012 version of Resik V “Sekarang Berhijab” advertisement using Roland Barthes’s semiotics theory. The results show that the advertisement utilizes the symbols of the hijab and the Indonesian Ulema Council’s label as commodities to put the Resik V product closer to Islam, as Islamic values attracted great attention from the society at that time that leaded to consumption activity. However, the Islamization in the Resik V product has ruled out the context of the hijab and halal concepts themselves, namely faith.